Morphological aspects of compounding: the case papaúpa - Maldonado Alegre, Fernando (2014)
The article focuses on analyzing and explaining word formation by composition in Peruvian Spanish. We pretend to establish morphosyntactic mechanisms that contribute to word formation, emphasizing morphological aspects of the compound word “papaúpa”; given that the lexical construction, without a doubt, is one of the linguistic facts that demonstrates a higher freedom from the speaker to form new terms. Within Peruvian Spanish, new linguistic structures are being generated in order to satisfy different ways of communication. Therefore, composition plays an important role in the growth of lexical repertoire.